Molecular Imaging of Invasive Pulmonary Aspergillosis Using ImmunoPET/MRI: The Future Looks Bright - Thornton, Christopher R. (Frontiers in Microbiology, 2018)
Invasive pulmonary aspergillosis (IPA) is a life-threatening lung disease of immuno-compromised humans caused by the ubiquitous environmental mould Aspergillus. Biomarker tests for the disease lack sensitivity and specificity, and culture of the fungus from invasive lung biopsy is slow, insensitive, and undesirable in critically ill patients. A Computed Tomogram (CT) of the chest offers a simple non-intrusive diagnostic procedure for rapid decision-making, and so is used in many haematology units to drive antifungal treatment. However, radiological indicators that raise the suspicion of IPA are either transient signs in the early stages of the disease, or are not specific for Aspergillus infection, with other angio-invasive moulds or bacterial pathogens producing comparable radiological manifestations in a chest CT. Improvements to the specificity of radiographic imaging of IPA have been attempted by coupling CT and Positron Emission Tomography (PET) with [18F]FDG, a marker of metabolic activity well-suited to cancer imaging, but with limited use in invasive fungal disease diagnostics due to its inability to differentiate between infectious etiologies, cancer, and inflammation. Bioluminescence imaging using single genetically modified strains of Aspergillus fumigatus has enabled in vivo monitoring of IPA in animal models of disease. For in vivo detection of Aspergillus lung infections in humans, radiolabelled Aspergillus-specific monoclonal antibodies, and iron siderophores, hold enormous potential for clinical diagnosis. This review examines the different experimental technologies used to image IPA, and recent advances in state-of-the-art molecular imaging of IPA using antibody-guided Positron Emission Tomography/Magnetic Resonance Imaging (immunoPET/MRI).